Negotiating relevance in pre-operative assessments. (March 2018) - Benwell, Bethan; Rhys, Catrin S.
Abstract: Preoperative assessments provide an essential clinical risk assessment aimed at identifying patient risks and requirements prior to surgery. As such they require effective and sensitive information-gathering skills. In addition to physical examination, the preoperative assessment includes a series of routine questions assessing a patient's fitness for surgery. These questions are typically designed to elicit minimal, 'no problem' responses, but patients sometimes produce expanded responses that extend beyond the projected information. Our analysis reveals that troubles-telling is often invoked by both nurses and patients as an effective, patient-centred resource for negotiating the medical relevance of patients' concerns in these contexts. Highlights: In preoperative assessments, questions are typically checklist oriented. Patients don't always respond within the constraints of checklist questioning. Nurses & patients use troubles-telling as a resource for negotiating relevance. Troubles-telling is a patient-centred resource for curtailing unnecessary detail.